A Review of Mineralogical Identification of Ayurvedic Rasa Dravyasa in Modern Context (AYUSHDHARA, 2024)
The metals and mineral drugs in Rasashastra are primarily categorized into different groups such as Maharasa, Uparasa, Sadharanarasa, Dhatu, Sudha, Sikta, and Ratna. These categories describe their origins, acceptable properties, and the various processes involved in making drugs for therapeutic use as well as preparation of noble metals. In ancient times, the identification of raw drugs relied mainly based on sensory factors like color, smell, texture, and taste. However, this data alone is insufficient to establish universal standards for both raw drug identification and the scientific detection of adulteration in finished products. Today, a multitude of modern tools and techniques are available for identifying metals and minerals, such as nature, crystal habit, color, streak, cleavage, fracture, lustre, X-ray diffraction (XRD) analysis, X-ray fluorescence (XRF), scanning electron microscopy (SEM), transmission electron microscopy (TEM), chromatography, tenacity, transparency, magnetism, hardness, specific gravity (density), and fluorescence, chemical assay and markers. Thus, my present study is plan to evaluate and compile different data in term of modern parameters and results as well as Grahya lakschans (acceptable characters) for identifying mineral drugs in Rasa shastra.